Scale effects on spatial heterogeneity of herbaceous vegetation in desert steppe depend on plant community type - Xiaoan Zuo (Elsevier, 2021)
Spatial heterogeneity plays a crucial role in affecting the ecologial processes in natural ecosystems, yet how spatial heterogeneity of herbaceous vegetation in desert-grassland transitional zone varies with increased spatial scale are still poorly known. We measured plant height, density, species richness and aboveground plant biomass (AGB) at the small (0.25 × 0.5 km), medium (0.5 × 0.5 km) and large (0.5 × 1 km) spatial scales in two adjacent plant communities (shrub- and grass-dominated) in desert steppe, Inner Mongolia. We used the geostatistical methods to examine the magnitude and degree of spatial heterogeneity of herbaceous vegetation characteristics with the increasing scale in both two plant communities. We found that compared to grass-dominated community, shrub-dominated community had the lower plant height and density at the large scale, the higher AGB at the small or medium scale, and the lower species richness at all three scales. Plant height, density and AGB in grass-dominated community were higher at the large scale than at the small scale, but they did not differ across three scales in shrub-dominated community. Species richness in both two communities were higher at the small scale than at the medium or large scale. All vegetation characteristics at three scales had the higher spatial heterogeneity in shrub- than in grass-dominated community. Spatial heterogeneity of all vegetation characteristics in shrub-dominated community decreased from the small to the large scale, while their spatial heterogeneity of plant height, density and species richness in grass-dominated community increased with the increasing scale. Our study highlights that shrub encroachment can simplify community composition and amplify spatial heterogeneity of herbaceous vegetation at multiple scales. Scale effects on spatial heterogeneity of herbaceous vegetation in desert steppe are dependent on plant community dominated by shrub or grass.